2022
DOI: 10.4103/njcp.njcp_258_22
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Polymerization Times on Color Change, Translucency Parameter, and Surface Hardness of Bulk-Fill Resin Composites

Abstract: Background: Polymerization plays an important role in the optical and mechanical properties resin composite materials. Aim: The current study aimed to evaluate the effect of different polymerization times on the color change, translucency parameter (TP), and surface hardness of resin composites after thermocycling. Materials and Methods: Microhybrid resin composite (Filtek Z250; used in the control group) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Bin Nooh et al, Gonder and Fidan, and Kim et al 14,32,33 for example obtained comparable values but lower than those of Al Senan and Al-Nahedh and Lopes et al 31,35 This discrepancy may be ascribed to the 24 h storage in distilled water performed by the first group of studies and not from the second one. Water storage and specimens' hydration could have therefore affected materials' translucency.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Bin Nooh et al, Gonder and Fidan, and Kim et al 14,32,33 for example obtained comparable values but lower than those of Al Senan and Al-Nahedh and Lopes et al 31,35 This discrepancy may be ascribed to the 24 h storage in distilled water performed by the first group of studies and not from the second one. Water storage and specimens' hydration could have therefore affected materials' translucency.…”
Section: Discussionmentioning
confidence: 83%
“…Reveal HD Bulk-Fill is characterized by HD filler technology, which allows light to pass through the material, while Tetric N-Ceram is prepared with Assencio filler technology that experimentally increases its opacity. 32 Indeed, Tetric composites contain a wide variety of filler types, among them: barium aluminum silicate glass (an "isofiller"), ytterbium fluoride, spherical mixed oxide, 33 and a mightier photoinitiator than CQ to increase curing depth, called Ivocerin. 11,60 In the study of Al-Senan and Al-Nahedh, 31 Tetric N Ceram Bulk-Fill showed higher TP values than the other materials tested, probably due to the above-mentioned ytterbium trifluoride filler (also incorporated in Filtek One Bulk-Fill).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal cycling was the most common approach that applied to simulate the aging of dental materials during temperature fluctuations that occur in the mouth in previous studies (Gale and Darvell, 1999;Tavas et al, 2023). It was carried out at temperatures equivalent to the intraoral temperature, ranging from 5 °C to 55 °C, and 10,000 cycles might be equivalent to 1 year (Gonder and Fidan, 2022). Color change (ΔE00 value) and microhardness of the experimental CRs affected by aging were presented in Table 5 and Table 6.…”
Section: Discussionmentioning
confidence: 99%